STATUS OF PLASMA ELECTROLYTES, UREA, CREATININE, AND C-REACTIVE PROTEIN IN CANCER PATIENTS. - Ojo, Olubunmi C; Asaolu, Modupe F; Oyeyemi, Ajibade O; Akinlua, Ibikunle; Molehin, Olorunfemi M; Oyebanji, Olufisayo G (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Objective: Cancer is a major health problem not only in developed countries but also in developing countries like Nigeria. This study was designed to study the status of plasma electrolytes, urea, creatinine, and C-reative proteins (CRPs) in freshly diagnosed cancer patients. Methods: Plasma electrolytes (sodium [Na+], potassium [K+], chlorine [Cl-], and bicarbonate [HCO3-]), urea, creatinine, and CRP were estimated in four different types of cancer (liver, colon, cervical, and uterine) patients attending Ekiti State University Teaching Hospital Ado Ekiti Nigeria. A total of 250 patients (between age of 45 and 70 years) consisting of 50 patients in each cancer type and 50 normal subjects as control were considered in this study. Results: The result obtained revealed a significant (p<0.05) increase in the plasma levels of Na+, Cl-, creatinine, and CRP in all the cancer types when compared with the control subjects. Plasma urea level decreased significantly in patients with colon (3.16±0.70 mmol/L) and liver (3.03±1.75 mmol/L) cancer when compared with the control subjects (4.80±1.12 mmol/L). K+ and HCO3_ level was not significantly (p>0.05) different in all cancer types when compared with the control subjects. Conclusion: This study revealed a possible link between plasma electrolytes, creatinine, CRP, urea, and cancer which could be useful in the assessment and management of cancer.